Comparison of QIAstat-Dx and BioFire FilmArray Gastrointestinal Panels in a Pediatric Population - Mohammed Suleiman; Muhammad Iqbal; Patrick Tang; Andrés Pérez-López (Microorganisms)
Accurate laboratory diagnosis of gastroenteritis is important to ensure that patients receive appropriate treatment and proper isolation precautions. This study evaluated the performance of the QIAGEN QIAstat-Dx gastrointestinal panel (QGP) in comparison to the bioMerieux BioFire FilmArray gastrointestinal panel (BGP) for the detection of gastrointestinal pathogens in 110 pediatric patients being evaluated for gastroenteritis at our hospital. We compared 23 different bacterial, viral, and parasite enteropathogens detected by the QGP against the BGP. The overall positive percent agreement (PPA) for all compared targets was 96.2% and the overall negative percent agreement (NPA) for all compared targets was 99.7%. Our study shows that QIAstat-Dx QGP provides comparable results to the BioFire BGP in our pediatric population. Additionally, the PCR cycle threshold (Ct) value reported by the QGP is potentially a helpful tool in estimating the load of the detected pathogen in stool samples.